(untitled) (Lundiana: International Journal of Biodiversity, 2009)
Fragmentation and loss of forests is a global problem that negatively affects biological communities generating local extinction of species. Studies of communities in disturbed areas are important to provide information on new ensembles of birds that are established there. In 56 campaigns carried out during 1991-2002, 272 species of birds were recorded, belonging to 59 families. Five of the species are threatened and 43 endemic (21% of all the species endemic to the Atlantic Forest). The most abundant species were those related to disturbed habitats with the greatest species richness recorded in the mixed forest of laurel and guatambú with 142 species, the forest margins with 139 species and the human settlements with 133 species.